Contribution of Spiritual Intelligence, Work Culture, and Interpersonal Communication to the Performance of Christian Religious Education Teachers in Manado City - Baideng, Novdian H.S.; Lolombulan, Julius; Lumi, Deflita R.N. (International Journal of Education, Information Technology, and Others, 2024)
The leading aspect of achieved quality education requires the role of teachers as educators, who are professional and dignified. Realized the fundamental and strategic role and position of humans in determining or-ganizational success, a high level of teacher performance is need in every aspect of the education sector. This research aims to determine the contribution of the variable spiritual intelligence, work culture and interpersonal communication to teacher performance, both individually and in pairs. Validity testing was carried out in 2 ways, namely by logical validity testing by getting input from experts to improve the instruments, and the empirical validity testing on 25 respondents. Meanwhile, overall reliability obtained a score of more than 0.7, which means it is reliable. Furthermore, the results of the validity and reliability testing, the items declared invalid will be discarded and not used in further research. So, this instruments analysis with valid items continued to obtain research data involving 82 Christian religious education teachers in Manado City. The results of the analysis using multiple regression were obtained variables whose significance was less than 0.05 was work culture on teacher performance, which means work culture contributed to teacher performance, spiritual intelligence and work culture together contributed to teacher performance, work culture, and interpersonal communication. -together contribute to teacher performance, spiritual intelligence, work culture, and interpersonal communication jointly contribute to teacher performance.Contribution, spiritual intelligence, work culture, interpersonal communication, teacher performance.